10 Cyber-Warfare Threats and How to Fight Back. (21st August 2019) - Unknown
Abstract: The BCS North London Branch recently hosted an event by Professor Claudio Cilli of the University of Rome. His presentation detailed the complexities of cyber warfare, advanced persistent threats (APT) and what can be done to defend our precious networks and infrastructure